Selected works of D. T. Suzuki - Suzuki, Daisetz Teitaro (University of California Press, 2020)
Daisetsu Teitaro Suzuki's writings introduced Buddhism to much of the world outside Asia. The fourth volume, Buddhist Studies, presents nineteen writings on Buddhist studies in three parts: the "Early Years," "Otani Years," and "Mature Years." In these pieces, Suzuki seeks to clarify the Mahayana Buddhist doctrines in Indian, Chinese, and Japanese historical contexts.